Physical activity in an air-polluted environment: behavioral, psychological and neuroimaging protocol for a prospective cohort study (Healthy Aging in Industrial Environment study - Program 4) - Elavsky, S; Jandačková, V; Knapová, L; Vašendová, V; Sebera, M; Kaštovská, B; Blaschová, D; Kühnová, J; Cimler, R; Vilímek, D; Bosek, T; Koenig, J; et al. (BMC public health, 2021)
BACKGROUND: Air pollution has been linked to increased mortality and morbidity. The Program 4 of the Healthy Aging in Industrial Environment study investigates whether the health and wellbeing benefits of physical activity (PA) can be fully realized in individuals living in highly polluted environments. Herein, we introduce the behavioral, psychological and neuroimaging protocol of the study. METHODS: This is a prospective cohort study of N = 1500 individuals aged 18-65 years comparing: (1) individuals living in the highly polluted, industrial region surrounding the city of Ostrava (n = 750), and (2) controls from the comparison region with relative low pollution levels in Southern Bohemia (n = 750). Quota sampling is used to obtain samples balanced on age, gender, PA status (60% active runners vs. 40% insufficiently active). Participants are screened and complete baseline assessments through online questionnaires and in-person lab-based assessments of physiological, biomechanical, neuroimaging and cognitive function parameters. Prospective 12-month intensive monitoring of air pollution and behavioral parameters (PA, inactivity, and sleep) follows, with a focus on PA-related injuries and psychological factors through fitness trackers, smartphones, and mobile apps. Subsequently, there will be a 5-year follow-up of the study cohort. DISCUSSION: The design of the study will allow for (1) the assessment of both short-term variation and long-term change in behavioral parameters, (2) evaluation of the incidence of musculoskeletal injuries and psychological factors impacting behavior and injury recovery, and (3) the impact that air pollution status (and change) has on behavior, psychological resilience, and injury recovery. Furthermore, the integration of MRI techniques and cognitive assessment in combination with data on behavioral, biological and environmental variables will provide an opportunity to examine brain structure and cognitive function in relation to health behavior and air pollution, as well as other factors affecting resilience against and vulnerability to adverse changes in brain structure and cognitive aging. This study will help inform individuals about personal risk factors and decision-makers about the impact of environmental factors on negative health outcomes and potential underlying biological, behavioral and psychological mechanisms. Challenges and opportunities stemming from the timing of the study that coincided with the COVID-19 pandemic are also discussed.
Keywords: Male; znečištění ovzduší; lidé středního věku; výzkumný projekt; Neuroimaging; Pyrimidines; Prospective Studies; Surveys and Questionnaires; zdravé chování; Humans; pyrimidiny; Air Pollution; Middle Aged; senioři; látky znečišťující vzduch; neurozobrazování; mužské pohlaví; prospektivní studie; Exercise; Female; COVID-19; mladiství; Health Behavior; Air pollution; Research Design; Aging; Aged; zdravé stárnutí; Physical activity; ženské pohlaví; průzkumy a dotazníky; Air Pollutants; mozek; mladý dospělý; Adult; Resilience, Psychological; Young Adult; Environment; cvičení; psychická odolnost; Adolescent; Brain; dospělí; lidé; Cognition; Healthy Aging; Health; kognice